The covid-19 epidemic in China - Lau, Lawrence J.; Xiong, Yanyan (World Scientific, 2021)
This book contains an in-depth quantitative analysis of the development of the COVID-19 epidemic in China from its very beginning in December 2019 to early April 2020 when it was brought under control. It begins with adjustments of the official cumulative data on newly confirmed cases and deaths, removing any inconsistencies and smoothing the surges not attributable directly to the COVID-19 virus itself. It discusses the measures undertaken by the Chinese Government to control the epidemic. It examines the extent of the infection, the case mortality, and the costs to the Chinese economy in both Hubei, the province in which the first confirmed case was discovered, and the rest of the Mainland outside of Hubei. There is also an international comparison of the Chinese experience with those of other countries.